Harvesting Harmony of Socio-Economic Interactions in Fostering Sustainable Agrotourism: A Case Study in Tambi Tourism Village, Wonosobo, Central Java - Mawar Setya Ningrum; Nawang Widyhasworo; Apriyani Muntikawati (International Journal of Geography, Social, and Multicultural Education, 2026)
Sustainable agrotourism development depends not only on environmental preservation but also on the effective integration of socio-economic dynamics in rural communities. This study explores how social and economic interactions support sustainable agrotourism in Tambi Tourism Village, Central Java, known for its historic tea plantations and strong agrarian identity. Using a qualitative case study method, supported by field observations, stakeholder interviews, and SWOT analysis, the research identifies how collaboration among local actors ensures tourism growth while maintaining social inclusion and environmental balance. The SWOT analysis highlights key strengths such as strong community engagement, preserved agro-cultural heritage, and structured management through Village-Owned Enterprises (BUMDes). Challenges include limited infrastructure, digital illiteracy, and seasonal dependency. Opportunities lie in the rising demand for ecotourism, government policy support, and the potential of digital platforms to strengthen rural branding. Threats include climate change, cultural commodification, and increasing competition. The study proposes a sustainability model based on three pillars: inclusive economic participation through cooperatives and training; eco-conscious tourism grounded in local agricultural practices; and adaptive innovation through multi-stakeholder partnerships and digital integration. Tambi’s case illustrates that fostering socio-economic harmony is key to building resilient agrotourism, offering both local benefits and broader relevance for sustainable rural development across the Global South.